PENGARUH FAKTOR KOMUNIKASI DAN KOMITMEN ORGANISASI TERHADAP PENCAIRAN DANA APBN DENGAN PENGGUNAAN KARTU KREDIT PEMERINTAH MELALUI KINERJA APARATUR SEBAGAI VARIBEL INTERVENING (STUDI PADA SATUAN KERJA KEMENDIKBUDRISTEK) - I Dewa Gede Sayang Adi Yadnya (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of communication factors and organizational commitment (work units) on the disbursement of APBN funds using government credit cards through the performance of the apparatus as an intervening variable (study in the Ministry of Education, Culture, Research, and Technology). The research approach used in this research is a quantitative approach. Quantitative research methods aim to test the established hypotheses. This type of research is causal effect research. Causal effect research is research that aims to determine the relationship or influence between two or more variables. The exact number of the population is not known. Respondents in this study were 100 people in the work unit within the Secretariat General of the Ministry of Education, Culture, Research, and Technology with respondents spread across Jakarta, Medan, Palembang, Bandung, Yogyakarta, Semarang, Surabaya, Denpasar, Makassar, Padang, Banjarmasin, Aceh, Jayapura and Gorontalo. The data in this study were obtained by distributing the G-Form questionnaire given to the WhatsApp group. The data analysis used a Structural Equation Model (SEM) approach with the help of smart PLS applications. The results of the study show that, 1) Organizational Communication Affects the Disbursement of State Budget Funds with the use of government credit cards; 2) Organizational commitment affects the disbursement of APBN funds by using government credit cards; 3) Organizational Communication Affects Apparatus Performance; 4) Organizational Commitment Affects Apparatus Performance; 5) Apparatus performance affects the disbursement of APBN funds by using government credit cards; 6) Apparatus Performance is able to mediate the relationship of Organizational Communication to the Disbursement of APBN funds by using government credit cards and 7) Apparatus Performance is able to mediate the relationship of Organizational Commitment to the Disbursement of APBN funds with the use of government credit cards. It is recommended that each division be able to understand their respective duties and responsibilities related to the readiness of documents to be submitted for submission of APBN funds.